A Korean Exorcism: Charismatic Christian Exorcism or Shamanic Exorcism? Driving out Demons or Women? - Hong, Kyung (2015)
The charismatic Christian exorcism is a culturally constituted Christian hegemonic power practice in the belief of the actions of spirits while driving the ritual recipient to more subservience alongside irrevocable damages rather than actual healing. This paper discusses a form of Korean charismatic Christian exorcism, anchal-gido, focusing particularly on recent incidents in the Korean diasporic community across the U.S. Excessively adhered to exorcism which is a culturally similar aspect with the shamanic tradition in the belief of the actions of spirits, the ritual recipients in this form of exorcism are predominantly women who admit themselves to be demon-possessed and, therein, willing to yield themselves to the ritual so as to satisfy the masculine divine, husband, and stereotypical gender role. Involving physical touching from mildly laying hands on the body to extreme assaults frequently causes fatal injuries. As far as the belief in the spirits fits in the hegemonic power, the life of Korean diasporic women remains as the willing prey to demons of both human and divine worlds. In this regard, this paper also discusses the analogous characteristics in Korean shamanism along with the cultural location of Korean women, therein, compelling them to be willing victims in religious sectors.
Keywords: Diasporic Community; Faith-Based Violence; Korean Exorcism; Korean Shamanism; Women; harismatic Christian Healing Ritual